"WEARING ONE’S HEART ON HIS SLEEVE” : THE FORMATION AND EVOLUTION OF A (SHAKESPEAREAN) PROVERBIAL PHRASE - Doyle, Charles Clay (Proverbium - Yearbook, 2014)
The proverbial phrase “wear one’s heart on his sleeve” derives from a line in Shakespeare’s Othello. It has taken on a variety of meanings and acquired variants in wording, most notably, the common substitution of an abstract noun for the metaphorical heart, and the fre-quent replacement of wear with hang or pin. The image of pinning to the sleeve has its own history, which antedates Shakespeare’s play.